Visualizing Non Infectious and Infectious Anopheles gambiae Blood Feedings in Naive and Saliva-Immunized Mice - Choumet, Valerie; Attout, Tarik; Chartier, Loïc; Khun, Huot; Sautereau, Jean; Robbe-Vincent, Annie; Brey, Paul; Huerre, Michel; Bain, Odile (PLOS ONE, 2012)
Background Anopheles gambiae is a major vector of malaria and lymphatic filariasis. The arthropod-host interactions occurring at the skin interface are complex and dynamic. We used a global approach to describe the interaction between the mosquito (infected or uninfected) and the skin of mammals during blood feeding. Methods Intravital video microscopy was used to characterize several features during blood feeding. The deposition and movement of Plasmodium berghei sporozoites in the dermis were also observed. We also used histological techniques to analyze the impact of infected and uninfected feedings on the skin cell response in naive mice. Results The mouthparts were highly mobile within the skin during the probing phase. Probing time increased with mosquito age, with possible effects on pathogen transmission. Repletion was achieved by capillary feeding. The presence of sporozoites in the salivary glands modified the behavior of the mosquitoes, with infected females tending to probe more than uninfected females (86% versus 44%). A white area around the tip of the proboscis was observed when the mosquitoes fed on blood from the vessels of mice immunized with saliva. Mosquito feedings elicited an acute inflammatory response in naive mice that peaked three hours after the bite. Polynuclear and mast cells were associated with saliva deposits. We describe the first visualization of saliva in the skin by immunohistochemistry (IHC) with antibodies directed against saliva. Both saliva deposits and sporozoites were detected in the skin for up to 18 h after the bite. Conclusion This study, in which we visualized the probing and engorgement phases of Anopheles gambiae blood meals, provides precise information about the behavior of the insect as a function of its infection status and the presence or absence of anti-saliva antibodies. It also provides insight into the possible consequences of the inflammatory reaction for blood feeding and pathogen transmission.